A high intensity focused ultrasound system for veterinary oncology applications - Spanoudes, Kyriakos; Evripidou, Nikolas; Giannakou, Marinos; Drakos, Theocharis; Menikou, George; Damianou, Christakis A. (My University, 2021)
Background: Magnetic resonance-guided focused ultrasound surgery is an incisionless energy-based thermal method that is used for ablating tumors in the veterinary clinic. Aims and Objectives: In this article we describe a prototype of a veterinary system compatible with magnetic resonance imaging intended for small-to-medium-sized companion animals that was developed and tested in vivo in adult rabbits. Methods: Real-time monitoring of the ablation during the experiment was possible with MR thermometry. Experiments involved thermal monitoring of sonications applied in the thigh of the rabbits. A 38-mm diameter transducer operating at 2.6 MHz was used with a 60-mm-focal length. The robotic system employed 3 linear axes and one angular axis. For this study, only X and Y axis were enabled. Due to the target size limitations, motion in Z and Θ was not needed. The functionality of the positioning device was evaluated by means of MR thermometry, demonstrating sufficient heating and accurate motion in both axes of operation. Results: The postmortem findings confirm the ability of the system to induce thermal ablations in vivo in the absence of adverse effects. Conclusions: The device is a reliable and affordable solution for companion animal hospitals, offering and additional tool for the veterinary oncology society.
Keywords: Rabbit; Ultrasound; Veterinary oncology